Evaluasi Manajemen Limbah Padat Dan Cair Di Rsud Mimika - Misgiono, Misgiono; Setiani, Onny; Budiyono, Budiyono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2014)
Background: RSUD Mimika has implemented its solid and waste management. However, it has not been implemented properly. This research aimed to evaluate the solid waste and waste water management from input, process and output aspects. Methods: The research applied an observational technique from the input, process, to output stages. The research attempted to find out problems during the management of solid waste and waste water. Data consisted of primary data from observation and secondary data from documents. The data processing was done by comparing them according to the hospital waste management standards to find out whether problems arise, which can be used for giving recommendation to waste-related problem-solving. Results: The research resulted in as follows: no waste management for 821 kilograms of 95 drug items; 54.31 kg/day (92%) of medical solid wastes were well managed; 4.5 kg/day (8%) of medical solid wastes were poorly managed; 101.9 kg/day (96.8%) of non medical solid wastes were well managed; 3.1 kg/day (3.2%) of non medical solid wastes were poorly managed. The hospital produced 35.56 m3/day of waste water and excessive 9.11 mg/l NH3-free waste water. Conclusion: solid waste and waste water management at RSUD Mimika had not been effectively and efficiently implemented due to problems related to input, process and output aspects. Keywords: Hospital, Solid Waste, Waste Water, Input, Process, Output.